One Nonparabolic End Theorem on Kähler Manifolds (Communications in Mathematical Research, 2021)
In this paper, the complete noncompact Kähler manifolds satisfying theweighted Poincaré inequality are considered and one nonparabolic end theorem whichgeneralizes Munteanu's result is obtained.